2018
DOI: 10.1111/ahe.12372
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the motor neuron somata of geniohyoid muscle in rat: A horseradish peroxidase study

Abstract: The aim of the study was to investigate the location of motor neuron somata of geniohyoid muscle in rat. Nine Sprague-Dawley rats were used in this study. Operations were performed under general anaesthesia. Nembutal sodium, 40 mg per kg intraperitoneally was used for anaesthesia. 0.02 to 0.05 ml of 30% horseradish peroxidase (Sigma Type VI) solution in normal saline was injected into the exposed right geniohyoid muscle. After 48 hr, the animals were fixed by perfusion through left ventricle of heart, first by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Targeting this swallow microcircuit via activation of only one PiCo-related neuron type, ChAT or Vglut2, does not reliably trigger swallows under CIH conditions, unlike control room air conditions (A. D. Huff et al, 2023). To understand the complex disruption of CIH on swallow pattern generation it is important to note that we are measuring changes in two muscle complexes which spread among three motor neuron pools: hypoglossal nucleus, trigeminal nucleus, and nucleus ambiguus (Badran et al, 2005; Bieger & Neuhuber, 2006; Kemplay & Cavanagh, 1983; Razlan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting this swallow microcircuit via activation of only one PiCo-related neuron type, ChAT or Vglut2, does not reliably trigger swallows under CIH conditions, unlike control room air conditions (A. D. Huff et al, 2023). To understand the complex disruption of CIH on swallow pattern generation it is important to note that we are measuring changes in two muscle complexes which spread among three motor neuron pools: hypoglossal nucleus, trigeminal nucleus, and nucleus ambiguus (Badran et al, 2005; Bieger & Neuhuber, 2006; Kemplay & Cavanagh, 1983; Razlan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Variability in response to CIH on swallow motor pattern is reminiscent to the increased variability also seen in the generation of the respiratory motor pattern (Garcia et al, 2017; Garcia et al, 2016). To understand the complex disruption of CIH on the swallow motor pattern, it is important to note that we are measuring changes in two muscle complexes which spread among three motor neuron pools: hypoglossal nucleus, trigeminal nucleus, and nucleus ambiguus (Badran et al, 2005; Bieger & Neuhuber, 2006; Kemplay & Cavanagh, 1983; Razlan et al, 2018). There was no statistical difference in the probability of triggering a swallow during optogenetic stimulation of ChATcre:Ai32, Vglut2cre:Ai32 and ChATcre:Vglut2FlpO:ChR2 neurons in mice exposed to room air (Huff et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Innervation to the suprahyoid muscles was not dissected for naked mole‐rats in the present study, but is presumably similar to what has been previously shown in other rodents such as rats (Greene, ) and Bathyergids (Woods, ). The geniohyoid muscles are innervated by the hypoglossal nerve (CN XII; Greene, ; Razlan, Ullah, Kapitonova, Liaqat Ali Khan, & Fuad, ; Woods, ). The mylohyoid, anterior belly of the digastric, and transverse mandibular muscles share innervation from the mylohyoid nerve (a branch of the inferior alveolar nerve, which itself is a branch of the mandibular division of the trigeminal nerve, CN V; Greene, ; Woods, ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the right and left geniohyoid muscles originated from the rostromedial extents of the right and left hemi‐mandibles (close to the mandibular symphysis) to attach to the hyoid bone in naked mole‐rats (Figure e, black arrows). The geniohyoid muscles assist with movements of the mandible and the hyoid in other rodents, particularly during swallowing (Razlan et al, ), and may affect lower incisor movement in naked mole‐rats. Based on the orientation and attachment sites of each, the geniohyoids likely assist with rostroventral movement of the each hemi‐mandible and lower incisor (Figure b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation